Residential care in Germany for refugee young people - Struck, Norbert (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
This article analyzes developments in the forms of social work with young refugees and the legal framing of such work in Germany from 1990 to the present. In particular, it addresses the reactions of politicians and the child and youth welfare system to the sharp rise in the number of refugees in 2015 and 2016, and the concomitant significant increase in the number of unaccompanied minor refugees. It underlines the need for an approach based on children’s rights, and the necessity for social workers, especially those involved in helping youth, to resist the policies of deterrence that are aimed at keeping refugees out of Germany.